Pengembangan E-Modul Praktikum Getaran Harmonis Sederhana Berbantuan Aplikasi Phyphox untuk Melatih Keterampilan Proses Sains Siswa - Defitasari, Wahyu; Wahyuni, Siti (Universitas Negeri Semarang, 2024)
The purpose of this study was to determine the characteristics and feasibility of the simple harmonic vibration practicum e-module assisted by the Phyphox application, the level of students' science process skills after using the e-module, and students' responses to the e-module. The method in this study is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The subjects of this study were 60 students of class XI MIPA 5 and XI MIPA 6 SMAN 1 Tengaran who were taken by purposive sampling techniques. Data collection is carried out using questionnaires and tests. This study obtained the following results: (1) the results of the E-module practicum validation test by experts obtained a percentage of 73,44% with feasible criteria; (2) the results of students' science process skills were obtained by an average percentage of 78.96% who met the good criteria; and (3) the results of the student response test to the practicum e-module obtained a percentage of 87.25% with excellent criteria. Judging from these results, the simple harmonic vibration practicum e-module assisted by the phyphox application in this study is declared valid and can be used to train students' science process skills.